Obtaining Efficient Fully Simulatable Oblivious Transfer from General Assumptions - David, Bernardo M.; Nascimento, Anderson C. A.; Tonicelli, Rafael (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2011: Anais do XI Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2011)
We introduce a general construction of fully simulatable oblivious transfer based on lossy encryption. Furthermore, we extend the common definition of lossy encryption by introducing the notion of computationally lossy encryption. If the cryptosystem used is computationally lossy, our general construction yields oblivious transfer protocols with computational security for both parties. Otherwise, when regular statistically lossy cryptosystems are employed in this construction, it yields oblivious transfer protocols with statistical security for the sender. The construction introduced in this paper is realizable from rerandomizable, homomorphic and lossy cryptosystems in general. Thus, it yields specific constructions based on different assumptions, such as DDH, LWE and McEliece. Moreover, it proves the equivalence of fully simulatable oblivious transfer and lossy encryption.